2017
DOI: 10.1111/1749-4877.12207
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of habitat requirements of small rodents and effectiveness of an ecologically‐based management in a hantavirus‐endemic natural protected area in Argentina

Abstract: Hantavirus pulmonary syndrome is a severe cardio pulmonary disease transmitted to humans by sylvan rodents found in natural and rural environments. Disease transmission is closely linked to the ecology of animal reservoirs and abiotic factors such as habitat characteristics, season or climatic conditions. The main goals of this research were: to determine the biotic and abiotic factors affecting richness and abundance of rodent species at different spatial scales, to evaluate different methodologies for studyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The empirical testing and comparison of the efficacy of different rodent control methods on zoonotic risk mitigation is fundamental to designing the most efficient, costeffective, bioethical and environmentally safe control programs that will work at short and long term. In other fields of rodent control (e.g., crop protection, ecological conservation, development of control methods) studies similar to the ones necessary for zoonosis control are a well-established research field that can serve as a guide to the endeavor ahead (Jakel et al 2017, Jakel et al 2015, Tabak et al 2015, Vadell et al 2017. It is also clear that designing and reporting health-related studies can benefit from standardization of parameters to increase the public health benefit yielded from the studies.…”
Section: Discussionmentioning
confidence: 99%
“…The empirical testing and comparison of the efficacy of different rodent control methods on zoonotic risk mitigation is fundamental to designing the most efficient, costeffective, bioethical and environmentally safe control programs that will work at short and long term. In other fields of rodent control (e.g., crop protection, ecological conservation, development of control methods) studies similar to the ones necessary for zoonosis control are a well-established research field that can serve as a guide to the endeavor ahead (Jakel et al 2017, Jakel et al 2015, Tabak et al 2015, Vadell et al 2017. It is also clear that designing and reporting health-related studies can benefit from standardization of parameters to increase the public health benefit yielded from the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the published literature on rodent ecology in the region (Andreo et al, 2009;Fraschina et al, 2012;González Fischer et al, 2012;Vadell & Gómez Villafañe, 2016;Vadell et al, 2017;Maroli et al, 2021), we recorded 14 environmental variables that could potentially influence the presence and abundance of small rodents. Climate, land cover and topography data were compiled for Buenos Aires province from different online sources using QGIS 3.4 (QGIS DT, 2018).…”
Section: Environmental Datamentioning
confidence: 99%
“…Though much has been studied about the ecology of this species in some particular sites (Busch & Kravetz, 1992;Gorosito et al, 2020;Maroli et al, 2018;Maroli et al, 2020;Mills et al, 1992;Muschetto et al, 2018), and there have been some insights on the variations in the structure of rodent assemblages in the region (González Fischer et al, 2012, its abundance and habitat associations throughout its distributional area are not well known. As well as for other cricetid rodents of the region, its abundance has been associated with environmental and climatic factors such as precipitation, temperature, land use and tree cover (Andreo et al, 2009;Fraschina et al, 2012;González Fischer et al, 2012;Vadell & Gómez Villafañe, 2016;Vadell et al, 2017;Maroli et al, 2021). In the Ciervo de los Pantanos National Park, in northeastern Buenos Aires, O. flavescens is mainly found in the riparian forest (Carballido et al, 2011;Gómez Villafañe et al, 2012;Maroli et al, 2018), but throughout Buenos Aires province it is also commonly found in grasslands and cropfield borders (Fraschina et al, 2012;González Fischer et al, 2012;Leveau et al, 2006).…”
Section: Introductionmentioning
confidence: 99%